Development of The "Arkanuh" Application to Enhance Elementary School Students' Understanding of The History of Prophet Noah - Mochamad Fadhillah Yusup Fauzan; Pratiwi Tarida; Dina Marlina Sudrajat; Rezki Cladesvina Adhi Putri; Ani Nur Aeni (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
This study aims to develop and test the feasibility and effectiveness of the ARKANUH application, an augmented reality (AR)-based learning media on the story of Prophet Noah for second-grade elementary school students. This research employed the Design and Development (D&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were second-grade students of SDN Pataruman, Darmaraja District, Sumedang Regency. Data collection techniques included expert validation questionnaires, observation, pre-test, post-test, and interviews. The validation results from media experts reached a percentage of 86.5% (very good) and from material experts 84.2% (good), indicating that the application is feasible to use. The product trial showed an improvement in student understanding with an average N-Gain score of 0.6966 (69.66%), which falls into the moderately effective category with a moderate–high increase. Student and teacher responses were highly positive regarding the ease of use and appeal of the application. Thus, the ARKANUH application is proven effective in improving learning outcomes and providing an interactive, visual learning experience that supports the development of positive character in students. This study recommends the use of the ARKANUH application as an alternative learning media for Islamic Religious Education materials at the elementary school level.